2020
DOI: 10.1089/neu.2019.6551
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cerebral Perfusion Pressure: Targeted Treatment for Severe Traumatic Brain Injury

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Continuous monitoring of dCA parameters derived from robust ICP and CPP signals has been proven to be a very interesting and potentially helpful tool in comatose patients with severe TBI. 114 In retrospective studies, individual deviation from autoregulation guided CPP (CPPopt) levels was associated with poor clinical outcome. Hypoperfusion was associated with mortality and hyperperfusion with severe disability at six months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous monitoring of dCA parameters derived from robust ICP and CPP signals has been proven to be a very interesting and potentially helpful tool in comatose patients with severe TBI. 114 In retrospective studies, individual deviation from autoregulation guided CPP (CPPopt) levels was associated with poor clinical outcome. Hypoperfusion was associated with mortality and hyperperfusion with severe disability at six months.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoperfusion was associated with mortality and hyperperfusion with severe disability at six months. 114 In the same line of thought, it would be reasonable to think that evaluating dCA in IS, ICH, and SAH patients using the principle of individualized autoregulation guided treatment could overcome complications, adjust cerebral perfusion needs and improve the clinical outcome. However, as pointed out in our review, the main method used in the studies is TFA, which is a method that, at present, is so far not tested to monitor and guide clinical management using dCA information in real time at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…6 The distribution of the feature space with increasing ICP years [19]. Single-center multimodal research (n = 81) on ICP, arterial blood pressure (ABP) and cerebral perfusion pressure (CPP) monitoring (n = 81) was conducted by V. Petkus et al demonstrated that age older than 45 years and average ICP above 21.3 mmHg at all monitoring times were associated with unfavorable outcomes in an individual patient [20]. Although some limitations exist, a fixed threshold can serve the role of a successful targeted therapy well.…”
Section: Discussionmentioning
confidence: 99%
“…The initial clinical care and subsequent intensive care unit (ICU) care can substantially impact the morbidity and mortality of these patients. Periods of hypotension along with raised intracranial pressure (ICP) have been linked to increased mortality and worse outcomes in patients with severe TBI [ 2 6 ]. The 2016 Brain Trauma Foundation guidelines recommend treating ICP >22 mmHg and maintaining systolic blood pressure (SBP) >90 mmHg [ 7 ].…”
Section: Introductionmentioning
confidence: 99%